Toksisitas Ekstrak Daun Sirih Merah pada Tikus Putih Penderita Diabetes Melitus (TOXICITY OF RED BETEL EXTRACT IN DIABETIC WHITE RAT ) - Kendran, Anak Agung Sagung; Gelgel, Ketut Tono Pasek; Pertiwi, Ni Wayan Linda; Anthara, Made Suma; Dharmayuda, Anak Agung Gde Oka; Anggreni, Luh Dewi (Jurnal Veteriner; Vol 14 No 4 (2013), 2013)
The aim of this research was to study the toxicity of red betel  (Piper crocatum) extract in diabeticwhite rat based on ALT and AST activities. This research used 20 male white rats, which randomlydivided into five groups, P1: given only aqua; P2: given alloxan 120mg/kg bw; P3: given alloxan 120 mg/kgbw and red betel leaf extract 50 mg/kg bw; P4: given alloxan 120 mg/kg bw and red betel leaf extract 100mg/kg bw; P5: given alloxan 120 mg/kg bw and glibenclamide suspension 1 mg/kg bw. ALT and ASTactivities were measured by using reflovet plus Machine. The collected data were analyzed by usinganalysis of covariance. The result showed no significant  effect (P>0.05) was observed on giving red betelleaf extract in diabetic white rat for ALT and AST activities.  It can be concluded that red betel leaf extractis potential for diabetic treatment in white rat  and it is not toxic for the rat’s ALT and AST activities.
Keywords: Red betel leaf, diabetes mellitus, ALT and AST activity